2020
DOI: 10.7759/cureus.12374
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Comfort With Procedural Skills Performance Based on Elective Experience and Career Interest

Abstract: IntroductionDespite increased efforts, studies suggest that exposure to procedural skills in undergraduate medical training is insufficient. As medical students have low self-reported competence in many skills, a significant concern is that medical students are underprepared for a clerkship. Furthermore, pre-clerkship electives selected based on student career interests can provide students with additional skills learning opportunities. The impact of career interest and elective choice on student comfort with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Students with prior exposure to both dissection and prosection were more comfortable with the appearance of formaldehyde donors than the students that had no previous exposure to human donors. This may be due to the concept of increased experience leading to increased comfort (Garavatti et al, 2018;Huo et al, 2020). This difference could be due to increased experience with donors, specifically formaldehyde embalmed donors leading to habituation of negative external stimuli surrounding the donors.…”
Section: Discussionmentioning
confidence: 99%
“…Students with prior exposure to both dissection and prosection were more comfortable with the appearance of formaldehyde donors than the students that had no previous exposure to human donors. This may be due to the concept of increased experience leading to increased comfort (Garavatti et al, 2018;Huo et al, 2020). This difference could be due to increased experience with donors, specifically formaldehyde embalmed donors leading to habituation of negative external stimuli surrounding the donors.…”
Section: Discussionmentioning
confidence: 99%
“…The impending integration of artificial intelligence in medical practice makes it more important than ever for medical practitioners to acquire fine motor and procedural skills to be marketable [11]. Yet, medical students have low selfreported competence in many procedural skills, leaving them feeling unprepared for clerkships [12,13]. Unfortunately, existing literature suggests this is not addressed during the clerkship years.…”
mentioning
confidence: 99%
“…We see pre-clerkship electives as alternative short-term solutions that offer students with valuable learning opportunities to supplement the existing core curriculum. A previous study demonstrated that students who complete electives in procedural skills report being more comfortable with and demonstrate improved skills in performing procedures by the end of the course [12]. It also provides institutions with an incubator in which they can create, test, and optimize different content and modalities of delivery-before offering it to the larger population of medical students through the core curriculum.…”
mentioning
confidence: 99%